"Every picture tells a story": |an analysis of the crime-atrocity-murder illustrations in Servet-i Fünun as recurrent messages emphasizing a critique of the west - Emre, Side. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
The current study of Side Emre which is titled as "Every Picture Tells A Story: An Analysis of the Crime-Atrocity-Murder lllustrations in Servet-i Fiinun as Recurrnet Messages Emphasizing A Critique of the West" endeavoured to analyze and interpret several disconnected issues of the illustrated Ottoman popular periodical Servet-i FÜnun published in the years 1891, 1892, 1893 and 1895. The main focus ofthe study lied on the interpretation of the textual and illustrative materials of Servet-i Fiinun with a gradual condensation on the crime-atrocity-murder illustrations and articles. Chapter I dealt with the first three issues for the aim of tracing the character and format of the periodical. The "texture" of the periodical was analyzed via a synthetic and comparative method. Chapter fl, dealt with a number of thematically categorized illustrations of Servet-i Fünun, to expose various "visual channels of Westernization" that were being utilized. This chapter proposed several sub-branches of visual channels under the "foreign" and the "domestic" agenda. The final chapter of this study was about the textual and compositional interpretations of the "crime-atrocity-murder" illustrations with the aim of deciphering the messages emphasizing a criticism of the West. The main channel of research in this study consisted of a thorough and minute examination of first-hand sources in Ottoman Turkish and English. Several issues of Servet-i Fünun, Musavver Cihan, Malumat, Hazine-i Fünun, The Levant Herald and The Oriental Express were analyzed. The Appendix sections disclose the Turkish transcriptions of the examined issues of Servet-i Fünun and Musavver Ciban. Apart from that, the Press Memoirs of Ahmed ihsan Tokgoz, "Matbuat Hatıralarım" and "Tahsin Paşa'hn Yıldız Hatıraları, Sultan Abdülbamid" were the only bibliographical materials that were referred to in this study.
Keywords: Turkish newspapers -- History.; Turkish newspapers -- Illustrations -- History.